Role of physical activity in the occurrence of falls and fall-related injuries in community-dwelling adults over 50 years old - Pereira, Catarina L. N. (2014)
Purpose: This study examined the effect of the type, level and amount of physical activity in falls and fallrelated injuries. Method: Participants were 506 community-dwelling adults aged >50 years (390 women: 67.7 ± 6.8 years and 116 men: 69.6 ± 6.6 years). Falls, fall-related injuries (slight and severe), and physical activity (type, level and energy expenditure) were evaluated by questionnaires. Confounders included comorbidities, fear of falling, environmental hazards and physical fitness. Results: After adjustment for confounders, logistic analysis revealed that the likelihood of falling decreased by 2% for each 100 metabolic expenditure (MET-min/week) of total physical activity and increased by 5% for each 100 MET-min/week of vigorous-intensity physical activity; total physical activity >1125 MET-min/week and vigorous physical activity <500 MET-min/week were identified as cut-off values discriminating non-fallers from fallers. Compared to the low physical activity level, increased physical activity levels diminished the likelihood of the occurrence of severe fall-related injuries by 76% (moderate) and 58% (high; p < 0.05) in fallers. Conclusions: Being active, especially sufficiently active, reduces fall-related injuries by decreasing falls and by safeguarding against severe injuries when falls occur. At least 1125 MET-min/week of total physical activity including >500 MET-min/week of vigorous intensity seems to prevent falls and, therefore, fall-related injuries.Implications for Rehabilitation Being sufficiently active reduces fall-related injuries by reducing falls and by safeguarding against severe injury when falls occur For each additional amount of total physical activity there is a corresponding direct (due to the effect of isolated physical actvivity) and indirect (due to the subject gaining in fitness) decrease in the risk of falling and thus injury. Vigorous physical activity leads to an increase in total physical activity; however, it also leads to an increase in the risk of falling and injury Total physical activity of at least 1125 MET-min/week with equal or lower than 500 MET-min/week (i.e. less than 1 h/week, according IPAQ criteria) of vigorous intensity significantly reduces falls and therefore injury